The Fc Receptor-Like 3 Polymorphisms (rs7528684, rs945635, rs3761959 and rs2282284) and The Risk of Neuromyelitis Optica in A Chinese Population. Issue 38 (September 2015) - Lan, Wenjing; Fang, Shaokuan; Zhang, Huimao; Wang, Dan Tong Jianmeng; Wu, Jiang
Abstract : Abstract: Neuromyelitis optica (NMO) appears to be a severe inflammatory demyelinating disease occurring in the central nervous system. Furthermore, the Fc receptor-like 3 ( FCRL3 ) gene was previously found to be susceptible for a certain inflammatory demyelinating diseases (such as multiple sclerosis). The present study, therefore, was aimed to explore the possible association of FCRL3 gene polymorphisms with susceptibility to NMO in a Chinese Han population. Seven single nucleotide polymorphisms (SNPs) of FCRL3 were, respectively, genotyped in 132 NMO patients and 264 healthy controls via PCR assay. Moreover, the t -test and the chi-square test were used to estimate the association between genetic mutations of FCRL3 and the risk of NMO with Statistical Analysis System (SAS) software (Version 9.0). It was demonstrated that FCRL3_3, 5, 6 and 8, SNPs were remarkably associated with susceptibility to NMO in both allelic [OR = 1.50 (95% CI: 1.11–2.03, P = 0.008), OR = 1.44 (1.07–1.94, P = 0.015), OR = 1.45 (1.08–1.95, P = 0.014), and OR = 2.01 (1.13–3.60, P = 0.016)] and homozygous models [OR = 2.19 (95% CI: 1.19–3.99, P = 0.010), OR = 2.09 (1.15–3.80, P = 0.014), OR = 2.04 (1.13–3.67, P = 0.016), and OR = 5.33 (1.02–27.9, P = 0.027)]. However, the other 4 SNPs, FCRL3_4, FCRL3_7, FCRL3_9, did not show the significant associations with NMO. Conclusions in the present study could be drawn that 4 SNPs in FCRL3 (FCRL3_3∗C, 5∗C, 6∗A, 8∗G) might account for increased risk of NMO in a Chinese-Han population. Nevertheless, further cohort studies are in demand to validate the association in the future.